Diminishing potential for tropical reefs to function as coral diversity strongholds under climate change conditions. Issue 11 (29th August 2021) - Adam, Arne A. S.; Garcia, Rodrigo A.; Galaiduk, Ronen; Tomlinson, Sean; Radford, Ben; Thomas, Luke; Richards, Zoe T.
Abstract: Aim: Forecasting the influence of climate change on coral biodiversity and reef functioning is important for informing policy decisions. Dominance shifts, tropicalization and local extinctions are common responses of climate change, but uncertainty surrounds the reliability of predicted coral community transformations. Here, we use species distribution models (SDMs) to assess changes in suitable coral habitat and associated patterns in biodiversity across Western Australia (WA) under present‐day and future climate scenarios (RCP 2.6 and RCP 8.5). Location: Coral reef systems and communities in WA. Methods: We developed SDMs with model prediction uncertainty analyses, using specimen‐based occurrence records of 188 hermatypic scleractinian coral species and seven variables to estimate present‐day and future changes to coral species distribution and biodiversity patterns in WA under climate change conditions. Results: We found that suitable habitat is predicted to increase across all regions in WA under RCP 2.6 2050, RCP 8.5 2050 and RCP 2.6 2100 scenarios with all tropical and subtropical regions remaining coral biodiversity strongholds. Under the extreme RCP 8.5 2100 scenario, however, a clear tropicalization trend could be observed with coral species expanding their range to mid‐high latitude regions, while a substantial drop in coral species richness was predicted at low latitude tropical coral reefs, such as the inshore Kimberley and offshore NW reefs. Despite the predicted expansion south, we identified a net decline in coral biodiversity across the WA coastline. Main conclusions: Results from the models predicted higher net coral biodiversity loss at low latitude tropical regions compared with net gains at mid‐high latitude regions under RCP 8.5 2100 . These results are likely to be representative of latitudinal trends across the Southern Hemisphere and highlight that increases in habitat suitability at higher latitudes may not lead to equivalent biodiversity benefits. Urgent action is needed to limit climate change to prevent spatial erosion of tropical coral communities, extinction events and loss of tropical ecosystem services.